2018
DOI: 10.5539/jsd.v11n3p123
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Fish Trade Flows in Africa

Abstract: Given that fish and fishery products are ranked among the most traded food commodities globally, with developing countries accounting for the bulk of the world’s fish exports, the analysis of fish trade flows is of key importance for any policy measure in the fisheries sector. This study evaluates the determinants of fish trade flows by applying the generalized gravity model. Using panel data covering a period of 14 years for 54 African countries, the gravity model is estimated using the Tobit regression to ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Various attempts have been made to analyse the demand for fish in both developed and developing countries even though research on the demand for fish disaggregated by species is relatively new in the developing countries (Dey, 2000). For instance, in Malawi the few empirical studies on demand for fish have focused on the demand for fish in general (Maganga et al, 2014), the determinants of the demand for various fish products (Nankwenya et al, 2017) and analysing the complementarity and trade-offs in consumer choice and demand for products of two tilapia species (Chikowi et al, 2020). A review of some literature for comparative analysis is presented in the subsequent paragraphs.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Various attempts have been made to analyse the demand for fish in both developed and developing countries even though research on the demand for fish disaggregated by species is relatively new in the developing countries (Dey, 2000). For instance, in Malawi the few empirical studies on demand for fish have focused on the demand for fish in general (Maganga et al, 2014), the determinants of the demand for various fish products (Nankwenya et al, 2017) and analysing the complementarity and trade-offs in consumer choice and demand for products of two tilapia species (Chikowi et al, 2020). A review of some literature for comparative analysis is presented in the subsequent paragraphs.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…A study by Chikowi et al (2020) looked at how fish attributes, market factors, and consumer characteristics affect consumer choices and demand for tilapia fish in urban Malawi, but it did not disaggregate the fish demand based on the major fish species consumed in Malawi. Another study on the demand for fish in Malawi was done by Nankwenya et al (2017) who analysed factors that affect the demand for four fish products namely; smoked fish, dried fish, tinned fish, and fresh fish. However, just like the study by Chikowi et al (2020), the study by Nankwenya et al (2017) did not disaggregate the demand for fish by fish species even though prices and consumer preferences for different species of fish differ according to the species of fish and fish products (Dey, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gravity model is known as the typical and successful approach for analyzing bilateral trade which has been formulated using the Newton's equation of gravity. Gravity model of trade is popular as the best tool to explain the trade flows using importer and exporter characteristics jointly with the variables which might support or limit the trade (Nankwenya, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They have found that the GDPs of trading partners, population, regional trade agreements, and the common border have a positive correlation and distance has a negatively link to the export. Nankwenya et al (2018) have attempted to disclose the fish trade determinants of Africa. They have found that the economic conditions of partner countries, populations, common border and exporter's fish production are positively linked to the exports whereas the fish production of importer and distance between partners are acted as barriers for fish trade of Africa.…”
Section: Introductionmentioning
confidence: 99%